PENGARUH PROMOSI JABATAN, PERSEPSI KEADILAN KOMPENSASI DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA KARYAWAN PT ADIRA DINAMIKA MULTIFINANCE CABANG BANJARNEGARA - Sakhur; NIrmala (Majalah Imiah Manajemen & Bisnis, 2020)
This research entitled "The Influence of Job Promotion, Perception of Justice Compensation and Physical Work Environment for Employee Satisfaction at PT Adira Dinamika Multifinance Banjarnegara branch". The purpose of this research was to determine the effect of the promotion promotion on job satisfaction of PT Adira Multifinance Dynamics Branch Employees, the significant influence of perceptions of fairness compensation on PT Adira Multifinance Dynamics Branch Banjarnegara employee job satisfaction, the effect of the significance of the physical work environment on PT Adira Dinamika Multifinance employee work environment Banjarnegara branch and which has the most influence between job promotion, perceptions of fairness of compensation and physical work environment towards job satisfaction of employees of PT Adira Dinamika Multifinance, Banjarnegara Branch . The analytical tool used in this study is path analysis. From this research it can be concluded: First, the hypothesis that states promotion has a significant influence on job satisfaction of employees of PT. Adira Multifinance Dynamics in Banjarnegara Branch, accepted. This is proven by t count of promotions is greater than t table (4,3991 > 2,0141). Second, the hypothesis that the perception of fairness compensation has a significant influence on the job satisfaction of PT. Adira Multifinance Dynamics in Banjarnegara Branch, accepted. This is evidenced by calculating perceptions of fairness compensation greater than t table (3,0936 > 2,0141). Third, the hypothesis that the physical work environment has a significant influence on job satisfaction of employees of PT. Adira Multifinance Dynamics in Banjarnegara Branch, accepted. This is evidenced by t counting the physical work environment greater than t table (2,2498 > 2,0141). Fourth, the hypothesis that job promotion has the greatest influence compared to perceptions of justice compensation and physical work environment on job satisfaction of employees of PT. Adira Multifinance Dynamics in Banjarnegara Branch, accepted. This is evidenced by the value of the proportional influence of the highest promotion compared to perceptions of justice compensation and physical work environment (0,3447 > 0,2578 dan 0,1484).